A Fluorophore Fusion Construct of Human Profilin I with Non-Compromised Poly(L-Proline) Binding Capacity Suitable for Imaging. Issue 7 (7th April 2017) - Nejedla, Michaela; Li, Zhilun; Masser, Anna E.; Biancospino, Matteo; Spiess, Matthias; Mackowiak, Sebastian D.; Friedländer, Marc R.; Karlsson, Roger
Abstract: Profilin is vital for actin organisation in eukaryotic cells. It controls actin filament formation by binding monomeric actin and numerous proteins involved in polarised actin assembly. Important for the latter is the interaction surface formed by the N- and C-terminal helices, which pack close to each other on one side of the molecule at a distance from the actin site and mediate binding to poly-proline sequences present in many of the targeted proteins. Via these interactions, profilin contributes to the spatiotemporal control of actin filament growth. Studies of profilin dynamics in living cells by imaging techniques have been hampered by problems to generate fusion constructs with fluorophore proteins without negatively impacting on its poly-proline binding. With the object to circumvent this problem, we have generated an internal fusion of profilin with the green fluorescent variant citrine, here referred to as citrine–profilin. The characterisation of citrine–profilin (CIT-Pfn) demonstrates that it has full capacity to interact with poly-proline and also binds phosphatidylinositol lipids and actin, albeit with 10 times reduced affinity for the latter. Imaging of living cells expressing CIT-Pfn showed a distribution of the fusion protein similar to endogenous profilin. Furthermore, CIT-Pfn rescued the phenotypes observed after the Crispr/Cas9 knockout of the profilin 1 gene, including the lost migratory capacity characterising the knockout cells. Based on this, we conclude that the CIT-Pfn construct will be useful as a tool for displaying profilin localisation in living cells and obtaining information on its dynamic organisation under different conditions and activations of the actin microfilament and microtubule systems. Graphical Abstract: Highlights: Profilin is an essential control element of actin polymerisation. In addition to actin, it binds proteins with certain poly-proline sequences. The fold of the N- and C-terminal helices is vital for the poly-proline interaction. Tagging to either end of the protein chain interferes with profilin function. We present an intramolecular fusion construct suitable for imaging that shows full poly-proline binding capacity.